Burnout Among First-Year Medical Students During COVID-19 Pandemic in Mexico: A Cross-sectional Study - Jezzini Martínez, Sofía; Martínez Garza, Javier Humberto; Quiroga Garza, Alejandro; Zarate Garza, Pablo Patricio; Jacobo Baca, Guillermo; Gutiérrez de la O, Jorge; Fuente Villarreal, David de la; Salinas Álvarez, Yolanda; Elizondo Omaña, Rodrigo Enrique; Guzmán López, Santos (Executive Committee of the International Journal of Medical Students, 2022)
Background: The coronavirus pandemic is an international public health emergency without precedence in modern history. It represents a challenge to the academic and psychological stability of students due to the changes it can cause in daily life. This study aimed to evaluate the prevalence and level of burnout in medical students caused by the academic and psychological instability that the pandemic represents. Methods: A cross-sectional prospective study was designed using the Maslach Burnout Inventory-Student Survey (MBI-SS). This evaluated the emotional exhaustion due to study demands, cynicism, and negative self-academic efficacy. This study was based in the school of medicine of the Universidad Autonoma de Nuevo Leon (UANL), in Monterrey, Mexico during the Spring semester 2020. Results: A total of 154 (93 women and 61 men) first-year medical students participated (response rate 36.4%). Burnout was identified in 14.9% (n=23), and high emotional exhaustion in 53.9% (n=83). Burnout was almost 4 times more likely to develop in men than in women (aOR = 4.8; 95% Confidence Interval=1.7-13.3) when considering age as a covariable in the multivariable model. Conclusion: Further epidemiological studies of burnout syndrome in medical students are needed, and schools should consider promoting mental health and making programs available for their students to help overcome the emotional and social challenges during the pandemic.